Psychostimulants - Koob, George F.; Arends, Michael A.; McCracken, Mandy; Le Moal, Michel (Neurobiology of addiction, 2020)
Psychostimulant drugs, such as cocaine and amphetamines, of the indirect sympathomimetic class have a long history as tonics and other preparations to allay fatigue and sustain performance. These drugs also have a long history of abuse and dependence. Abuse potential varies with the availability of the drug both environmentally and physiologically, with intravenous and smoked forms of both cocaine and amphetamines producing much more severe substance use disorder. Cocaine and amphetamines have a characteristic abuse cycle that involves binge administration, withdrawal dysphoria, paranoia, and psychosis-like symptoms as the cycle continues or intensifies. Significant advances have been made in our understanding of the mechanisms of action of psychomotor stimulant drugs at the behavioral, neuropharmacological, cellular, and molecular levels that can be heuristically framed in the three-stage cycle of addiction: binge/intoxication, withdrawal/negative affect, and preoccupation/anticipation. Eventually, three corresponding domains and neurocircuits coalesced around these three stages: binge/intoxication (incentive salience/pathological habits domain, basal ganglia neurocircuits), withdrawal/negative affect (negative affect domain, extended amygdala), and preoccupation/anticipation (executive function, prefrontal cortex). Thus, the new revised book, Neurobiology of Addiction, is now organized along the three stage/three domain construct while retaining synthesis at the circuit, cellular, and molecular levels of analysis.